A Novel Approach Based on DEMATEL Method for Causal Modeling an Effective Factors in Falling from Height Accidents in Construction Projects - Sahram Vosoughi; Sajjad Rostamzadeh; Mohammad Hossein Chalak; Ali Asghar Farshad; Masoud Jahanpanah (Iranian Journal of Health, Safety and Environment, 2020)
Falling from height known as one of the most important factors that leads to fatal accidents in the construction industry. The purpose of this study was to investigate and identify the effective factors in the occurrence of falling from height accidents in the construction projects and determine the causal relationships between organizational, individual and environmental factors. In this research, the surveyed population was the workers of five construction projects of a gas refinery in south of Iran from 2011 to 2015. Using the Integrated Management System (IMS) information, factors and sub-factors affecting the occurrence of falling from height accidents in the construction projects were determined. Then, a semi-comparative questionnaire based on the DEMATEL technique was designed and distributed among 10 experts at two different periods. Based on the expert's opinions, the identified factors and sub-factors were classified into three main factors and fourteen sub-factors, respectively. Then, the causal relationships between each the effective factor were identified, using DEMATEL technique. The results of DEMATEL technique revealed that the individual factors were considered to be the most important criteria, as it has acquired the maximum (D+R) value, i.e., 36.689 whereas, organizational factors had scored the least, i.e., 35.180. Accordingly, organizational factors and their sub-factors had a substantial effect on the falling from height accidents and were considered as causal variables (D-R>0), while, the indices of individual and environmental factors were the effect variables (D-R